(untitled) (International Journal of Physiotherapy, 2015)
Background: Stroke-related balance and gait deficits contribute to the large number of falls in these patients. This may be due to inappropriate reaction to external forces. Hence, one has to be able to react to external forces with appropriately timed and scaled responses to maintain balance. Therefore it is important to identify which patients have risk of falling and would benefit from fall prevention measures. To accomplish this, valid and reliable clinical scales those are easy to administer are needed. Assessment scales that predict falls have been tested in different populations. The present prospective study compares two simple scales viz. Timed Up and Go test (TUG) and Performance Oriented Mobility Test (POMA) in fall prediction among patients with sub acute and chronic stroke. Methodos: 50 stroke subjects were asked to perform both the tests viz. TUG and POMA one after another on the date of evaluation or Day 0 and from Day 1 falls are recorded per month up to six months. Both test results were compared for their accuracy. Results: It was found that t = -4.496 which is highly significant at (p=0.00) which proves that there is remarkable difference in means of TUG and POMA. TUG covers 0.970 and POMA covers 0.135 area in the curve and is an established fact that higher area indicates excellent accuracy. The sensitivity and specificity of TUG is 78% and 94% respectively and that of POMA is 90% and 60% respectively. Conclusion: To conclude, we can say that there is significant difference between the Timed Up and Go test and Tinetti‘s Performance Oriented Mobility Assessment score on prediction of fall in Hemiparetic Stroke patients.